If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -1) = 2(2x + 4) Reorder the terms: -2(-1 + x) = 2(2x + 4) (-1 * -2 + x * -2) = 2(2x + 4) (2 + -2x) = 2(2x + 4) Reorder the terms: 2 + -2x = 2(4 + 2x) 2 + -2x = (4 * 2 + 2x * 2) 2 + -2x = (8 + 4x) Solving 2 + -2x = 8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + -2x + -4x = 8 + 4x + -4x Combine like terms: -2x + -4x = -6x 2 + -6x = 8 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + -6x = 8 + 0 2 + -6x = 8 Add '-2' to each side of the equation. 2 + -2 + -6x = 8 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = 8 + -2 -6x = 8 + -2 Combine like terms: 8 + -2 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| (-1/3a^3)(-1/9a^7) | | 4mp=2r | | 4mp=2y | | 9+2x=4.5x | | 3y=5x-13 | | 48/12=4/x | | 35x=2y | | 13=sqrt(a^2+144) | | P=11-b+c | | 3+2lnx=13 | | x=6x-17 | | -s=3s^2-2 | | 4-3(2-x)=7 | | ×/8=-9 | | (-4y^4)(5y^3)= | | x+10=46 | | 6x=30+3(x-4) | | -7x-37=-5x-35 | | -(2z-2)-(4z-8)+4=-4(z-9)-(9z+7)+9 | | 69/x=24 | | 5w+15=3w+1 | | -3/4x=9.4=0 | | (4x)(2x^8)= | | 7u+33=-3u+3 | | 8z-2(z-8)=6(z+1)+5 | | -2/5x=6/65 | | -×/2=8 | | X-y-2z=a | | 3z+3(z-2)=7z-3(z-10) | | (2x)(6x)= | | z+0.2=0.6(z+3) | | 5.2q-4.5-5.6q=-1.4q-3.7 |